STRATEGI PEMASARAN JASA PENDIDIKAN DALAM MENINGKATKAN DAYA SAING FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN PONOROGO - Nafi’ah, Ayu Zahroh; Ngadhimah, Mambaul (IAIN Ponorogo, 2024)
AbstractCompetition among higher education institutions requires overall cost leadership, product differentiation, and user focus. Marketing management is very necessary in universities to build a positive image in maintaining consumer satisfaction. The aim of this research is to describe the marketing of educational services in improving the existence and image of educational institutions, as well as the implementation of the 7P marketing mix at the Faculty of Islamic Economics and Business IAIN Ponorogo. This qualitative descriptive research chose the FEBI IAIN Ponorogo object because it has innovation and product differentiation for graduating students. Interview techniques with internal parties supported by observation and documentation are tools for exploring data. Interactive model analysis is carried out with the stages of data reduction, data presentation and drawing conclusions. The first research finding, the educational service mix strategy is a service activity that aims to maintain customer satisfaction through excellent service, providing quality education and learning, strengthening character education to produce competitive graduates. secondly, the Faculty of Islamic Economics and Business IAIN Ponorogo applies the 7P marketing mix, namely product, promotion, location, price, people, process and infrastructure as a marketing mix strategy to produce graduates of sharia bankers, sharia accountants and sharia microeconomic developers who are internationally competitive and have excellence, competitive, supported by the availability of lecturers, educational staff, infrastructure, various types and programs to develop student talents and interests, affordable costs, and use of digital platforms. AbstrakPersaingan antar institusi pendidikan tinggi memerlukan kepemimpinan biaya secara keseluruhan, diferensiasi produk, dan fokus pengguna. Manajemen pemasaran sangat diperlukan pada perguruan tinggi untuk membangun citra positif dalam menjaga kepuasan konsumen. Tujuan penelitian ini adalah untuk mendeskripsikan pemasaran jasa pendidikan dalam meningkatkan eksistensi dan citra lembaga pendidikan, serta penerapan bauran pemasaran 7P di Fakultas Ekonomi dan Bisnis Islam IAIN Ponorogo. Penelitian deskriptif kualitatif ini memilih objek FEBI IAIN Ponorogo karena memiliki inovasi dan diferensiasi produk bagi lulusan mahasiswa. Teknik wawancara dengan pihak internal yang didukung dengan observasi dan dokumentasi merupakan alat untuk menggali data. Analisis model interaktif dilakukan dengan tahapan reduksi data, penyajian data dan penarikan kesimpulan. Temuan penelitian pertama, strategi bauran layanan pendidikan merupakan kegiatan pelayanan yang bertujuan untuk menjaga kepuasan pelanggan melalui pelayanan prima, penyelenggaraan pendidikan dan pembelajaran yang bermutu, penguatan pendidikan karakter hingga menghasilkan lulusan yang berdaya saing. Kedua, Fakultas Ekonomi dan Bisnis Islam IAIN Ponorogo menerapkan bauran pemasaran 7P yaitu produk, promosi, lokasi, harga, manusia, proses dan infrastruktur sebagai strategi bauran pemasaran untuk menghasilkan lulusan bankir syariah, akuntan syariah dan pengembang mikroekonomi syariah yang berdaya saing internasional dan mempunyai keunggulan. kompetitif, didukung oleh ketersediaan dosen, tenaga kependidikan, infrastruktur, berbagai jenis dan program untuk mengembangkan bakat dan minat mahasiswa, biaya terjangkau, dan pemanfaatan platform digital.